Normative perceptual estimates for 91 healthy subjects age 60–75: impact of age, education, employment, physical exercise, alcohol, and video gaming - Wilms, Inge L.; Nielsen, Simon (Frontiers in Psychology, 2014)
Visual perception serves as the basis for much of the higher level cognitive processing as well as human activity in general. Here we present normative estimates for the following components of visual perception: the visual perceptual threshold, the visual short-term memory capacity and the visual perceptual encoding/decoding speed (processing speed) of Visual Short-Term Memory (VSTM) based on an assessment of 91 healthy subjects aged 60-75. The estimates were modelled from input from a whole-report assessment based on A Theory of Visual Attention (TVA). In addition to the estimates themselves, we present correlational data, and multiple regression analyses between the estimates and self-reported demographic data and lifestyle variables. The regression statistics suggest that education level, video gaming activity and employment status may significantly impact the encoding/decoding speed of VTSM but not the capacity of VSTM nor the visual perceptual threshold. The estimates will be useful for future studies into the effects of various types of intervention and training on cognition in general and visual attention in particular.